EFFORTS TO IMPROVE MATHEMATICS LEARNING ACTIVITIES USING THE EVEN COOPERATIVE LEARNING MODEL TYPE JIGSAW OF STUDENT SMP IN CLASS VII-E - Marlina Noor Utami; Romelan Hamzah (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2019)
Teacher-concerned learning students resulted in less active participation in learning mathematics. It is necessary to attempt to improve students learning activities. This study aims to improve mathematics learning activities using the cooperative learning model type of Jigsaw in class VII-E in State Junior High School (SMP Negeri) 1 Imogiri Bantul Regency of even semester year academic 2018/2019. This study was a classroom action research that consists of two cycles. This study's setting was students class VII-E of even in SMP Negeri Imogiri Bantul regency academic year 2018/2019. The method of collecting data used observation and interviews. The research instrument used an observation sheet and interview sheet. The test instrument used instrument validity and analysis of data used qualitative descriptive analysis. The results showed that the Jigsaw could improve mathematics learning activities in students class VII-E of even semester in SMP Negeri 1 Imogiri Bantul regency academic year 2013/2014. This is evident from the observation of studentâ€™s mathematics learning activities, and the average test scores have increased in each cycle. This can be seen from the average percentage of learning interactions in cycle I of 77,32 % with the right criteria increased in Cycle II, amounting to 85,34 %Â  with very good criteria.